1997
DOI: 10.1063/1.474957
|View full text |Cite
|
Sign up to set email alerts
|

The ammonia dimer spectrum in cold helium clusters

Abstract: Infrared molecular beam depletion spectroscopy has been used to measure the spectrum of ammonia dimers embedded in large helium clusters after the excitation of the umbrella mode. The spectral region from 940 to 1010 cm−1 was covered by a line-tunable CO2-laser. By measuring the dependence of the depletion signal on the pressure of the pick-up cell, we confirmed that all lines are caused by the dimer. The spectrum exhibits two groups of two lines at 978/983 and 992/997 cm−1 separated by 14 cm−1 with a line spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Homogeneous clusters which have been studied in the IR region include (SF 6 ) n [130,144] (n = 2-4), (HCCCN) 2 , [136] (CH 3 OH) n n = 2-5, [176] (CH 3 CN) n n = 2-6, [176] (HCN) n n = 2-7, [145,146] (HF) n n = 2-8, [177][178][179] and (H 2 O) n n = 2-6. [180][181][182] The number of heterogeneous van der Waals complexes studied is even larger and includes such systems as HCN-H 2 (parahydrogen (pH 2 ), ortho-hydrogen (oH 2 ), para-deuterium (pD 2 ), ortho-deuterium (oD 2 ), HD), [183,184] HCN-C 2 H 2 , [185] HCN-Mg n (n = 1-3), [152,186] HF-H 2 (pH 2 , oH 2 , pD 2 , oD 2 , HD), [187,188] and HF-Ar n (n = 1-6) (Ne,Kr), [189] and OCS-(H 2 ) n (n = 1-17). [148][149][150][151] In most of these systems rotational resolution has been achieved.…”
Section: Free Rotations Of Molecules and Clusters In Heliummentioning
confidence: 98%
“…Homogeneous clusters which have been studied in the IR region include (SF 6 ) n [130,144] (n = 2-4), (HCCCN) 2 , [136] (CH 3 OH) n n = 2-5, [176] (CH 3 CN) n n = 2-6, [176] (HCN) n n = 2-7, [145,146] (HF) n n = 2-8, [177][178][179] and (H 2 O) n n = 2-6. [180][181][182] The number of heterogeneous van der Waals complexes studied is even larger and includes such systems as HCN-H 2 (parahydrogen (pH 2 ), ortho-hydrogen (oH 2 ), para-deuterium (pD 2 ), ortho-deuterium (oD 2 ), HD), [183,184] HCN-C 2 H 2 , [185] HCN-Mg n (n = 1-3), [152,186] HF-H 2 (pH 2 , oH 2 , pD 2 , oD 2 , HD), [187,188] and HF-Ar n (n = 1-6) (Ne,Kr), [189] and OCS-(H 2 ) n (n = 1-17). [148][149][150][151] In most of these systems rotational resolution has been achieved.…”
Section: Free Rotations Of Molecules and Clusters In Heliummentioning
confidence: 98%
“…High power line-tunable gas lasers, cw or pulsed, are still being used up to the present time [59,60,61,62]. Because of the sparse set of available lasing frequencies, they are most suited to the investigation of small molecules, with small moments of inertia and therefore well spaced lines.…”
Section: Radiation Sourcesmentioning
confidence: 99%
“…It is remarkable that this process is repeated until the linear chain spans the whole cluster diameter, as the data of Nauta and Miller show. Observed spectra for CH 3 OH and CH 3 CN clusters [59], for H 2 O clusters [64] and for Ar n +HF clusters (described in their article in this issue [134]) have been interpreted as arising from the isomers which are formed with the smallest amount of nuclear rearrangement. So far this self-assembling technique has been applied using stable molecules.…”
Section: Special Topics a Synthesis Of Nonequilibrium Structuresmentioning
confidence: 99%
“…Analogs of these peaks in argonmatrix experiments have been studied by several workers, 19,26,27 and analyses of the spectrum of ͑NH 3 ͒ 2 between about 975 and 1010 cm −1 have been reported for the dimer in the gas phase 28 and in helium clusters. 29 Therefore, it is suggested that the addition of H 2 to the sample somewhat reduces the extent of isolation of NH 3 in neon. Although for a Ne: NH 3 = 800: 1 mole ratio the random probability of nearest-neighbor pairs of NH 3 molecules in the neon matrix is extremely small, some dimer formation can occur in the gas-phase sample and on the surface of the deposit.…”
Section: Concentration Dependence Of the Absorption Patternsmentioning
confidence: 99%